2019
DOI: 10.20950/1678-2305.2019.45.4.516
|View full text |Cite
|
Sign up to set email alerts
|

ECONOMIC FEASIBILITY FOR THE PRODUCTION OF LIVE BAITS OF LAMBARI (<i>Deuterodon iguape</i>) IN RECIRCULATION SYSTEM

Abstract: Sport fishing is a growing segment in the fishing sector in Brazil. It is, however, an activity that depends upon young shrimp and fish offer to supply live bait demand, its extraction might result on overfishing and compromise natural stock. The intensive cultivation in water recirculation system is a worldwide trend for aquaculture, which, in addition to increasing productivity, minimizes the impact of effluent emission on the environment, reinforcing sustainability. This study analyzed the economic viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, in one experiment conducted in small net-cages (160 L) over 45 days, Vilela and Hayashi [37] obtained 100% survival. Henriques et al [38] suggested that the Atlantic forest lambari (Deuterodon iguape) can attain 80 to 90% of survival raised in indoor recirculating tanks over 60 days. These data indicate the potential to increase the survival and yield of lambari culture by improving management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in one experiment conducted in small net-cages (160 L) over 45 days, Vilela and Hayashi [37] obtained 100% survival. Henriques et al [38] suggested that the Atlantic forest lambari (Deuterodon iguape) can attain 80 to 90% of survival raised in indoor recirculating tanks over 60 days. These data indicate the potential to increase the survival and yield of lambari culture by improving management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in one experiment conducted in small net-cages (160 L) during 45 days, Vilela and Hayashi [37] obtained 100% survival. Henriques et al [38] suggested that the Atlantic forest lambari (Deuterodon iguape) can attain 80 to 90% of survival raised in indoor recirculating tanks during 60 days. These data indicate the potential to increase the survival and yield of lambari culture by improving management practices.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly found in small rivers and streams of tropical and subtropical regions and is native to the Atlantic Forest watershed [40]. This species is widely used in the fishing market both for human consumption and for use as live bait in recreational fisheries [41,42]; mainly of tucunaré (Cichla spp.) and south american silver croaker (Plagioscion squamosissimus) [41,43], which helps to reduce juvenile shrimp fishing [44].…”
Section: Introductionmentioning
confidence: 99%